Comparative analysis of damages and defects in rails of different railway transport systems (Transport systems and technologies, 2023)
This article provides an analysis of the accumulation of detected damages and defects in the rails of two transportation systems - urban (metro) and mainline railway transport. Summarizing the analysis conducted, it should be noted that defects according to figures 10 and 11 are more often encountered on the tracks of the Kyiv Metro. At the same time, defects according to figure 27 are more often encountered on the tracks of the mainline railway transport, and it is also worth noting a wider range of defects, the share of which does not exceed 5%. According to the authors, this is related to the peculiarities of the conditions for operating transportation systems, particularly the load on the axle of the moving equipment, the movement characteristics, and other operational parameters. In order to make more accurate conclusions, it is necessary to perform a number of works using mathematical modeling methods to take into account the influence of individual parameters on the accumulation of defects and damages in rails.
Keywords: rolling stock, transport system, wheel pair, rail, railway track, defect, damage, fatigue, cracking.